Biocompatible Gold Nanoparticles Ameliorate Retinoic Acid-Induced Cell Death and Induce Differentiation in F9 Teratocarcinoma Stem Cells - Sangiliyandi Gurunathan; Jin-Hoi Kim (Nanomaterials, 2018)
The unique properties of gold nanoparticles (AuNPs) have attracted much interest for a range of applications, including biomedical applications in the cosmetic industry. The current study assessed the anti-oxidative effect of AuNPs against retinoic acid (RA)-induced loss of cell viability; cell proliferation; expression of oxidative and anti-oxidative stress markers, pro- and anti-apoptotic genes, and differentiation markers; and mitochondrial dysfunction in F9 teratocarcinoma stem cells. AuNPs were prepared by reduction of gold salts using luteolin as a reducing and stabilizing agent. The prepared AuNPs were spherical in shape with an average diameter of 18 nm. F9 cells exposed to various concentrations of these AuNPs were not harmed, whereas cells exposed to RA exhibited a dose-dependent change in cell viability and cell proliferation. The RA-mediated toxicity was associated with increased leakage of lactate dehydrogenase, reactive oxygen species, increased levels of malondialdehyde and nitric oxide, loss of mitochondrial membrane potential, and a reduced level of ATP. Finally, RA increased the level of pro-apoptotic gene expression and decreased the expression of anti-apoptotic genes. Interestingly, the toxic effect of RA appeared to be decreased in cells treated with RA in the presence of AuNPs, which was coincident with the increased levels of anti-oxidant markers including thioredoxin, glutathione peroxidases, glutathione, glutathione disulfide, catalase, and superoxide dismutase. Concomitantly, AuNPs ameliorated the apoptotic response by decreasing the mRNA expression of p53, p21, Bax, Bak, caspase-3, caspase-9, and increasing the expressions of Bcl-2 and Bcl-Xl. Interestingly, AuNPs not only ameliorated oxidative stress but also induced differentiation in F9 cells by increasing the expression of differentiation markers including retinoic acid binding protein, laminin 1, collagen type IV, and Gata 6 and decreasing the expressions of markers of stem cell pluripotency including Nanog, Rex1, octamer-binding transcription factor 4, and Sox-2. These consistent cellular and biochemical data suggest that AuNPs could ameliorate RA-induced cell death and facilitate F9 cell differentiation. AuNPs could be suitable therapeutic agents for the treatment of oxidative stress-related diseases such as atherosclerosis, cancer, diabetes, rheumatoid arthritis, and neurodegenerative diseases.